A Theology of Green Islam: Managerial System of Islamic Transformative Rehabilitation for Mental Disorder Patients - Aris Risdiana; Reza Bakhtiar Ramadhan (Universitas Islam Negeri (UIN) Salatiga, 2019)
This study seeks to explore the theological ideas of 'Green Islam' as the basis of the managerial system of Islamic transformative rehabilitation for students (santri) with mental disorders in Islamic boarding school (Pondok Pesantren/PP) Al Qodir. Easily, this theology implements psychological and sociological problems that undermine the human psyche through rehabilitation instruments. According to KH Masrur Ahmad, the theology of Green Islam is the basis for the contextualization of Islamic teachings that are friendly to weak people. The Islamic boarding school based model and based on local wisdom experience, integrated with the rehabilitation model which is a secular conception gave birth to a new paradigm related to the pattern of the managerial system of Islamictransformative rehabilitation in PP Al Qodir. While the process of Islamic rehabilitation there are three stages, namely self-cleaning, self-development, and self-improvement. By adopting the rehabilitation process, Green Islam is an effective therapy, as well as a rehabilitation management system that promotes transformative patterns. The success of applying theology is based on the POAC (Planning, Organizing, Actuating, and Controlling) technique that is attached to the figure of KH Masrur Ahmad as the caregiver of PP Al Qodir. G. R Terry emphasizes that managerial systems are a process of planning, organizing, mobilizing and controlling by utilizing knowledge and art in order to achieve previously set goals. So the purpose of this paper is to explore the pattern of the PP Al Qodir managerial system in rehabilitating santri who have mental disorders using the basis of theology of Green Islam. The results of this study indicate that the implementation of transformative Islamic rehabilitation is very dependent on the management of POAC developed by KH. Masrur Ahmad.